Resveratrol treatment restores peripheral insulin sensitivity in diabetic mice in a sirt1‐independent manner. Issue 8 (28th April 2015) - González‐Rodríguez, Águeda; Santamaría, Beatriz; Mas‐Gutierrez, José Antonio; Rada, Patricia; Fernández‐Millán, Elisa; Pardo, Virginia; Álvarez, Carmen; Cuadrado, Antonio; Ros, Manuel; Serrano, Manuel; Valverde, Ángela M.
<x xml:space="preserve">Abstract</x> Scope Mice with deletion of insulin receptor substrate (IRS) 2 develop hyperglycaemia, impaired hepatic insulin signaling and elevated gluconeogenesis. Protein tyrosine phosphatase 1B (PTP1B) inhibition by resveratrol improves peripheral insulin sensitivity of these mice. Although resveratrol activates Sirtuin1 (Sirt1), the mechanisms underlying its beneficial effects are not totally elucidated. In this study, we have investigated whether Sirt1 mediates the effects of resveratrol in controlling insulin resistance in diabetic mice. Methods and results We attempted to ameliorate peripheral insulin resistance in two diabetic models, Irs2‐deficient (Irs2−/−) mice and streptozotocin (STZ)‐injected mice by resveratrol treatment or Sirt1 overexpression. Resveratrol improved systemic insulin sensitivity of Irs2‐deficient mice. Irs2‐deficient mice are characterized by high levels of PTP1B expression in liver and muscle. Interestingly, resveratrol decreased PTP1B in both tissues, thereby restoring IRS1‐mediated insulin signaling. Moreover, resveratrol also restored insulin sensitivity and hepatic insulin signaling in STZ‐diabetic mice. In contrast, moderate overexpression of Sirt1 neither normalized PTP1B levels nor restored insulin signaling in Irs2‐deficient mice or STZ‐diabetic mice. Conclusion Resveratrol improves peripheral insulin signaling independently of Sirt1 in diabetic mice in association with the inhibition of PTP1B and, therefore, this polyphenol could be an effective adjuvant for the treatment of diabetes.